(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2024)
Public procurement plays a crucial role in the economic development of countries. This article reviews Uzbekistan’s public procurement system, focusing on its legal framework and structure of various procurement methods. The article explores international practices by reviewing the advanced procurement systems of South Korea and Germany and emphasizes their e-procurement platforms and sustainability-focused policies. The study suggests that Uzbekistan could significantly enhance its public procurement efficiency by adopting foreign practices. By implementing a robust e-procurement system and integrating sustainability criteria, Uzbekistan can modernize reduce corruption and promote sustainable development.